2007
DOI: 10.1007/s00216-007-1290-3
|View full text |Cite
|
Sign up to set email alerts
|

Dicationic ionic liquid stationary phase for GC-MS analysis of volatile compounds in herbal plants

Abstract: The seeming "dual nature" of ionic liquids (ILs) for separating both apolar and polar compounds suggests that ILs may have a great potential for complex samples like essential oils from herbal plants that contain a great variety of compounds. In the present work, a geminal dicationic IL, 1,9-di(3-vinylimidazolium)nonane bis[(trifluoromethyl)sulfonyl]imidate, was investigated for this purpose. To find the best way to achieve satisfactory separations simultaneously for the compounds in essential oils, the dicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
94
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(96 citation statements)
references
References 23 publications
0
94
0
Order By: Relevance
“…or organic anions (e.g., NTf2 − , TfO − , etc.). It has been reported that the amount of possible combinations of ionic liquids can be up to 10 18 , because their corresponding cationic/anionic moieties can be easily altered [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…or organic anions (e.g., NTf2 − , TfO − , etc.). It has been reported that the amount of possible combinations of ionic liquids can be up to 10 18 , because their corresponding cationic/anionic moieties can be easily altered [1].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with traditional monocationic ionic liquids, geminal ionic liquids exhibited higher thermal stabilities over 350 °C. The operating temperature ranges were also greatly expanded by using geminal ionic liquids as gas chromatographic stationary phases [18]. Moreover, polymerized ionic liquids [19], functionalized ionic liquids [20], and chiral ionic liquids [21] have been exploited in gas chromatography.…”
Section: Introductionmentioning
confidence: 99%
“…ILs form a relatively new class of stationary liquid phases that have some advantages, in particular, high thermal stability in comparison with other types of high-polar phases, polarity, and the possibility to control phase selectivity in a wide range [15,16]. Earlier it was shown that the use of columns with ILs provides good separations of various objects: fatty acids, oil products, objects of plant origin, and pesticides [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…A high contribution of specific interactions is typical of such ILs [16]. Thus, phases with such ILs are highly selective for polar compounds, particularly for phenols [16], which make columns with these phases attractive for separation of objects considered in this work.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, ILs are termed "designable solvents" [8], and various applications have reported for them. In analytical chemistry, ILs were used as stationary phases in gas chromatography [9][10][11], additives for capillary electrophoresis [12][13][14][15], matrices for MALDI [16][17][18], as well as solvents for spectral analysis [19][20][21] and electrochemistry [22]. Several reviews that focus on these topics have been published recently [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%